Maritime Security in the Anthropocene: How Indonesia Addresses the Intersection of Climate Change and Ocean Governance - Novitasari, Yussie; Irwanto, Bambang; Prakoso, Lukman Yudho (International Journal of Education, Vocational and Social Science, 2025)
This research aims to analyze the impact of climate change in the Anthropocene era on Indonesia's maritime security and to evaluate the capacity of marine governance in addressing these challenges. The method used is a Systematic Literature Review (SLR), analyzing various relevant literature from journals, policy reports, and institutional data related to climate change, maritime security, and marine governance. The results of the study indicate that climate change affects marine ecosystems, disrupts the socio-economic stability of coastal communities, and increases security risks, including threats to maritime sovereignty. Indonesia's marine governance capacity faces challenges such as policy fragmentation, weak inter-agency coordination, and limitations in infrastructure and human resources. To address these challenges, reforms in marine governance are recommended, including strengthening institutions, investing in technology and human resources, and implementing ecosystem-based policies. A collaborative approach involving local communities and international cooperation is also a strategic step towards creating sustainable, adaptive, and inclusive marine governance.